A Dinosaur Ichnocoenosis from the Waterberg Plateau (Etjo Formation, Lower Jurassic), Namibia. Issue 3 (1st October 2016) - Wagensommer, Alexander; Latiano, Marianna; Mocke, Helke B.; Porchetti, Simone D'Orazi; Wanke, Ansgar
ABSTRACT: About a hundred dinosaur tracks, mostly preserved as isolated footprints, have been recorded at a single site within the borders of the Waterberg National Park, Otjozondjupa Region, north-central Namibia. They are found in an interdune setting within the Lower Jurassic Etjo Formation and represent medium-sized theropods with slender digits and high projection of digit three. From an ichnotaxonomic point of view, the Namibian tracks are intermediate in morphology between Grallator (which is known to occur at other localities within the same Etjo Formation) and Anchisauripus, being otherwise in a size range that is usually considered typical for the latter ichnotaxon or even for Eubrontes . The Waterberg tracks do not match the allometric growth model proposed by Olsen et al. (1998) for the Early Jurassic theropod track assemblage of the North American Connecticut Valley, and they highlight the difficulties of consistently discriminating between theropod ichnotaxa in the Grallator-Anchisauripus-Eubrontes plexus. The Waterberg ichnosite adds important data to our understanding of the ichnological diversity of the Etjo Formation, raising to three the dinosaur localities in Namibia with revised and updated ichnofaunas. The dinosaur ichnofauna from Namibia, of which the Waterberg tracksite is a basic component, shows high ichnotaxonomic similarity with coeval assemblages from the northern hemisphere. This points to an overall homogeneity of the global ichnofaunistic composition, even at lower latitudes.